2009
DOI: 10.3329/jhpn.v27i3.3380
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Theories of Postpartum Bleeding in Matlab, Bangladesh: Implications for Community Health Intervention

Abstract: Early recognition can reduce maternal disability and deaths due to postpartum haemorrhage. This study identified cultural theories of postpartum bleeding that may lead to inappropriate recognition and delayed care-seeking. Qualitative and quantitative data obtained through structured interviews with 149 participants living in Matlab, Bangladesh, including women aged 18-49 years, women aged 50+ years, traditional birth attendants (TBAs), and skilled birth attendants (SBAs), were subjected to cultural domain. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This adaptation of the kanga is promising and consistent with findings from a study in Gambia that showed that TBAs distinguish between “normal” and “alarming” amounts of blood loss by using the number of lappas (pieces of cloth) soaked with blood in addition to assessing blood flow 23 . A third alternative, developed by the ICDDR, B and now included in the Matlab setting, is a special pad or diagnostic aid calibrated to help women and lay care‐givers identify a blood loss of 500 mL 16 . These pads are similar to those used by hospitals in the United States to absorb fluids.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This adaptation of the kanga is promising and consistent with findings from a study in Gambia that showed that TBAs distinguish between “normal” and “alarming” amounts of blood loss by using the number of lappas (pieces of cloth) soaked with blood in addition to assessing blood flow 23 . A third alternative, developed by the ICDDR, B and now included in the Matlab setting, is a special pad or diagnostic aid calibrated to help women and lay care‐givers identify a blood loss of 500 mL 16 . These pads are similar to those used by hospitals in the United States to absorb fluids.…”
Section: Discussionsupporting
confidence: 75%
“…A retrospective analysis was performed using existing data obtained from a larger study on the recognition of and response to PPH in Matlab, Bangladesh, in 2006 16 . Structured interview records from 149 participants, including SBAs, TBAs, and laywomen were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Several important misconceptions as to the causes of PPH were prevalent among the participants and have been previously described in studies from the region [33,34]. For example, evil spirits, were often held responsible for the occurrence PPH and, therefore, it was presumed that healing could be assisted in a better way by a kabiraj or spiritual healers.…”
Section: Discussionmentioning
confidence: 86%
“…Community members are often unable to recognize excessive bleeding particularly because of the absence of means to assess although they described a variety of methods for identifying excessive blood loss based on the amount or pattern of blood loss or other personal judgments. Similarly, another study from Bangladesh found that rural women often described excessive bleeding by the characteristics of blood flow [34]. Therefore, provision of specific tools and proper guidance at the community level is recommended to enable identification of bleeding that has become excessive.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration by researchers suggested that the principal reasons for not seeking care were related to concerns over medical costs and severe socioeconomic disparities [ 23 ]. Gross misunderstandings and misconceptions regarding PPH at the community level in Bangladesh also contribute to low access and uptake of care [ 24 26 ]. Among service providers, current methods to assess PPH are also suboptimal.…”
Section: Introductionmentioning
confidence: 99%